2012
DOI: 10.1371/journal.pone.0049549
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Protein Interactions and Complex Formation in the Pectobacterium atrosepticum Subtype I-F CRISPR/Cas System

Abstract: Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) and their associated proteins (Cas; CRISPR associated) are a bacterial defense mechanism against extra-chromosomal elements. CRISPR/Cas systems are distinct from other known defense mechanisms insofar as they provide acquired and heritable immunity. Resistance is accomplished in multiple stages in which the Cas proteins provide the enzymatic machinery. Importantly, subtype-specific proteins have been shown to form complexes in combination with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
80
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 54 publications
4
80
0
Order By: Relevance
“…1C). These results are consistent with pull-down experiments performed in the type I-F CRISPRCas system of Pectobacterium atrosepticum (20) and suggest that Cas1 interacts with the amino-terminal Cas2-like domain of the Cas2/3 fusion protein (22)(23)(24).…”
Section: Significancesupporting
confidence: 88%
See 2 more Smart Citations
“…1C). These results are consistent with pull-down experiments performed in the type I-F CRISPRCas system of Pectobacterium atrosepticum (20) and suggest that Cas1 interacts with the amino-terminal Cas2-like domain of the Cas2/3 fusion protein (22)(23)(24).…”
Section: Significancesupporting
confidence: 88%
“…In fact, early evidence supporting this functional overlap came from bioinformatic studies that identified a unique fusion in type I-F systems that links a Cas2-like adaptation protein to the amino terminus of the Cas3 interference protein (i.e., Cas2/3) (54). Indeed, Cas1 and Cas2/3 have been shown to interact in P. atrosepticum, but the structural and functional implications of the Cas2/3 fusion have not been determined (20). Here we show that Cas2/3 from P. aeruginosa stably associates with the Cas1 adaptation protein, forming a 375-kDa propeller-shaped complex consisting of two Cas2/3 proteins and four Cas1 proteins (Cas1 4 :Cas2/3 2 ) (Fig.…”
Section: Significancementioning
confidence: 66%
See 1 more Smart Citation
“…18 Furthermore, we have shown that a Csy interference complex is formed, composed of Csy1, Csy2, Csy3 and Cas6f. 19 The Csy complex also interacts with Cas2-Cas3, 19 which is likely to be recruited for target DNA unwinding and degradation.…”
Section: Crispr-cas Chromosomal Targeting Is Detrimental To the Host mentioning
confidence: 99%
“…The recent evidence that Cas1 and Cas2 from the related type I-E system are involved in acquisition 9 led to the proposal that the Cas1:Cas2-Cas3 complex is important for acquisition of new spacers. 19 Therefore, Cas2-Cas3 is hypothesized to play crucial roles in both acquisition and interference steps.…”
Section: Crispr-cas Chromosomal Targeting Is Detrimental To the Host mentioning
confidence: 99%